Power Discourse and Social Control in Orwell’s Nineteen Eighty-Four - Widaad, Hilmy Qaais (Journal of Literature, Linguistics, & Cultural Studies, 2024)
In the contemporary era, literary studies play a crucial role in understanding power dynamics within social contexts. This research analyzes the impact of power discourse on social practices portrayed in George Orwell's Nineteen Eighty-Four. Employing the discourse theory of power, the study reveals an intricate power system, showcasing its enduring nature, which makes overthrowing it challenging. Adopting a literary sociology approach, the researcher considers the socio-historical aspects of the novel's world. Data collection involves narratives and dialogues aligned with research objectives, drawing on Michel Foucault's theoretical concepts such as episteme, power/knowledge relations, disciplining (normalization), and panopticon. The research explores how power discourse significantly shapes social reality in Orwell's society, employing a critical analysis of the novel's narrative. Foucault's concept of epistemology examines the construction and maintenance of knowledge in the totalitarian government policies depicted. The interplay between power and knowledge raises inquiries into the control and utilization of information to uphold power structures. The discipline concept, focusing on normalization, analyzes the enforcement of obedience and conformity in a government-ruled society. Additionally, Foucault's panopticon notion scrutinizes how surveillance and control involve invisible elements influencing individual behavior. Through these analytical frameworks, the research unveils the intricate dynamics between power discourses and social practices in Nineteen Eighty-Four, offering profound insights into the exercise and maintenance of power in an authoritarian society.